Implementation and Benefits of Religious Moderation in Maintaining Faith and Preserving Harmony in Madrasah - Syahrin, Alif Alfi; Idris, Muhammad; Syahputra, Achmad Agung (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study aims to describe the implementation and practice of religious moderation in madrasahs and their surroundings, as well as the benefits of instilling religious moderation in students who live as Muslim minorities in Bali. The research method used is qualitative research with a phenomenological approach. The technique for determining informants used purposive sampling, consisting of the head of the madrasah, the deputy head of the madrasah, subject teachers, and ten students. Data were collected using participant observation techniques, structured interviews, and documentation studies. Primary data included the implementation and practice of religious moderation in the madrasah environment and the benefits felt based on observations and interviews. Secondary data consisted of data from previous studies, reports, and regulations related to the implementation of religious moderation, particularly in the madrasah environment. The data was analysed using an interactive model, namely data collection, data condensation, data presentation, and conclusion drawing. The results of the study show that the implementation of religious moderation at MAN Buleleng is through curriculum policy, subject integration, habit-forming programmes, religious programmes, social programmes, and leadership training. Furthermore, the practice of religious moderation includes respecting other people's holidays, interacting with people of different religions, attending institutional invitations, recruiting non-Muslim teachers, and distributing takjil (food to break the fast) across faiths during Ramadan. The benefits felt by students from the instilling of religious moderation can be classified into various dimensions, such as psychological, social, personal religious, citizenship, and inclusive attitudes. Various findings show that religious moderation has various benefits in the context of Muslim minorities as an effort to maintain faith and maintain harmony among religious communities.